Manejo de los desechos hospitalarios y su impacto en la calidad de vida de los habitantes del cantón Quevedo - Medina Bravo, Willian Miguel (2013)
This thesis is carried out in the Hospital sacred heart of Jesus and several Sub centers in the city of Quevedo, for the purpose of establishing the level of environmental pollution caused by the management of hospital waste and its impact on the quality of life of the inhabitants of the canton. The document comprises six chapters. The first focuses on the object of study, according to the needs of the investigation, be defines the reason for the investigation of laws, norms, rights and processes that regulate the management of hospital solid waste. In this section discusses the causes and effects of inadequate management of the waste generated at the Sub centers and Quevedo canton Hospital. It justifies the important thing is to apply the laws and processes of biosafety, with the purpose of optimizing the collection and selection of waste; the of ensuring the health of workers, inhabitants and the environment. The second chapter consists of the history of research, establishing a theoretical basis, according to the variables of objectives and hypotheses. Theories, doctrines and various scientific articles were cited in several books, texts and web sites, which strengthened the object of study. Chapter three, sample type, methods, techniques and instruments of research implemented to achieve the objectives and to verify the hypothesis. The fourth chapter, indicates the results of the field study, through statistical tables and systematized analysis showing percentage expressed opinions by partners them and directors of the medical units of the canton, concerning the knowledge of the laws and standards of biosecurity in the management of hospital solid waste. Chapter five establishes the respective conclusions and recommendations, whereas the results of the field study, doctrinal and legal. In chapter six, shown the proposal "Elaboration of a Municipal Ordinance that regulates the collection, transport, controls and treatment of hospital waste in the sector", which is intended to ensure respect for the rights of nature, as established by the Constitution in its article 71